Contractor’s Right Of Action For Late Or Non-Payment By The Employer - Judi, Siti Suhana; Rashid, Rosli Abdul (Journal of Surveying, Construction and Property, 2010)
Late or non-payment of interim payment to Contractors has been a major issue in the Malaysian Construction Industry. It has affected the performance of Contractors and has caused several of them not being able to complete the work on time thus causing delay in the completion of the project. In the worse scenario, they are forced to abandon their projects for lack of fund and some were on the brink of bankruptcy. This should not be the case because it is clearly stated in the various standard form construction contract used in Malaysia i.e. the PWD203A (Rev 1/83), PAM 1998/2006 and CIDB 2000, that the Contractors must be paid within 30 days, 14 days and 21 days after his receipt of the Interim Certificate respectively. Apart from arbitration, what other remedies available to the Contractor when he is not paid on time or have not been paid at all by the Employer. This paper is written based on a master thesis entitled “The Contractor’s Right of Action for Late or Non-Payment by the Employer”. The objective of the research is to determine the various actions that a Contractor can take in the event of late or non-payment by the Employer. The research focuses only on the issue of late or non-payment of Interim Certificate. It is based on the study of the PWD 203A (Rev 83), PAM 98/2006 and CIDB 2000, common law principles and case laws. This research carried out by adopting from combination of document analysis, case law and review of act and statute. This study involve in legal matter, which can only be carried out based on court decision which reported in MLJ, MLJA, MLJu etc and this study is more Qualitative research. The study suggested that a when faced with the problem of late or non-payment by the Employer the Contractor may either suspend the work, claim for interest, apply for summary judgment, apply for the winding up of the Employer’s company or he may determine the contract with the Employer. But consideration must be given to the actual construction of the contract and details of each case. Keywords: Interim payment, Contractors, Late payment, Non Payment, Construction Contract